Effect of aggregate and cementitious material on properties of lightweight self-consolidating concrete for prestressed members. (15th June 2015) - Floyd, Royce W.; Hale, W. Micah; Bymaster, Jared C.
Highlights: Expanded clay and shale aggregate self-consolidating concretes were studied. High cementitious materials contents are required to achieve adequate flow. Type III cement was required for high early-age strength. Elastic moduli were closely predicted using the ACI Code equation. Measured shrinkage was less than 50% of ACI 209 predictions. Abstract: Forty-one concrete mixtures were used to examine the effects of cementitious material and aggregate type and content on flow and compressive strength of expanded clay and shale lightweight self-consolidating concrete. Type III cement was required to produce compressive strengths in excess of 28 MPa at one day, and high cementitious materials contents were required for adequate fresh and hardened properties. A limiting difference in slump and J-Ring flow of 100 mm is recommended for similar concrete mixtures. Moduli of elasticity measured for selected mixtures were accurately predicted by the ACI equation, and shrinkage was less than predicted by typical models.